The Neural Mechanisms Underlying the Influence of Pavlovian Cues on Human Decision Making - Bray, Signe; Rangel, Antonio; Shimojo, Shinsuke; Balleine, Bernard; O'Doherty, John P (The Journal of neuroscience, 2008)
In outcome-specific transfer, pavlovian cues that are predictive of specific outcomes bias action choice toward actions associated with those outcomes. This transfer occurs despite no explicit training of the instrumental actions in the presence of pavlovian cues. The neural substrates of this effect in humans are unknown. To address this, we scanned 23 human subjects with functional magnetic resonance imaging while they made choices between different liquid food rewards in the presence of pavlovian cues previously associated with one of these outcomes. We found behavioral evidence of outcome-specific transfer effects in our subjects, as well as differential blood oxygenation level-dependent activity in a region of ventrolateral putamen when subjects chose, respectively, actions consistent and inconsistent with the pavlovian-predicted outcome. Our results suggest that choosing an action incompatible with a pavlovian-predicted outcome might require the inhibition of feasible but nonselected action–outcome associations. The results of this study are relevant for understanding how marketing actions can affect consumer choice behavior as well as for how environmental cues can influence drug-seeking behavior in addiction.